Photonic chiplet interconnection via 3D-nanoprinted interposer - Huiyu Huang; Zhitian Shi; Giuseppe Talli; Maxim Kuschnerov; Richard Penty; Qixiang Cheng (Light: Advanced Manufacturing)
In the past several decades, photonic integrated circuits (PICs) have been investigated using a variety of different waveguide materials and each excels in specific key metrics, such as efficient light emission, low propagation loss, high electro-optic efficiency, and potential for volume production. Despite sustained research, each platform shows inherit shortcomings that as a result stimulate studies in hybrid and heterogeneous integration technologies to create more powerful cross-platform devices. This is to combine the best properties of each platform; however, it requires dedicated development of special designs and additional fabrication processes for each different combination of material systems. In this work, we present a novel hybrid integration scheme that leverages a 3D-nanoprinted interposer to realize a photonic chiplet interconnection system. This method represents a generic solution that can readily couple between chips of any material system, with each fabricated on its own technology platform, and more importantly, with no change in the established process flow for the individual chips. A fast-printing process with sub-micron accuracy is developed to form the chip-coupling frame and fiber-guiding funnel, achieving a mode-field-dimension (MFD) conversion ratio of up to 5:2 (from a SMF28 fiber to 4 µm × 4 µm mode in polymer waveguide), which, to the best of our knowledge, represents the largest mode size conversion using non-waveguided 3D nanoprinted components. Furthermore, we demonstrate such a photonic chiplet interconnection system between silicon and InP chips with a 2.5 dB die-to-die coupling loss, across a 140 nm wavelength range between 1480 nm to 1620 nm. This hybrid integration plan can bridge different waveguide materials, supporting a much more comprehensive cross-platform integration.